Quoting and Self-Quoting - Falk, Lilian (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1992)
The present paper examines first-person quotations with a view to testing the hypothesis recently proposed by H. H. Clark and R. J. Gerrig in Language, Vol. 66, #4 (Dec. 1990) that quotations should be regarded as Selective Depictions rather than as Verbatim Reproductions of previous speech. The special conditions of self-quoting, where the speaker has privileged knowledge of the circumstances and details of previous occurrence, can shed additional light on the nature of quoting. The examples confirm the proposal of Selective Depictions, but they also indicate that the selective depiction is mainly a result of changes in circumstances between the previous speech and the new occasion on which previous speech is quoted by the same speaker.